O risível em Porta dos Fundos a carnavalização do discurso religioso judaico-cristão - Lima, Marília Dalva Teixeira de (2019)
This work aims to address one of the ways of constitution of the laughter in contemporary society in humor sketches of the Porta dos Fundos channel posted on the YouTube video platform. The object of study of this work is the carnivalesque sense of the world and the phenomenon of bivocality, as seen in the Bakhtinian work, existing in the skits of Porta dos Fundos, specifically in skits related to Judeo-Christian religiosity. From the 57 videos which present this theme, 11 were selected for this work: four of them are about texts related to biblical Old Testament texts, five to biblical New Testament texts and four skits which carnivalize the relation between religiosity and contemporary social themes. In these videos we analyze linguistic-discursive aspects such as word games, intonation, violation of social norms, characterization of characters (costumes, makeup etc), representation of diverse social types, stereotypes, inversions of social roles etc., which are essential to understand the processes that lead to the laughable from the skits analyzed, as well as the topics of the ridicule, stupidity and absurdity, which enable the carnavalization of the biblical text and the topics related to social criticism that contribute to the process of bivocalization. It tries to understand how the process of constitution of the risabable one takes place from the religious discourse and if there are traces of the carnivalesque laughter as proposed by Bakhtin (2013). The theoretical framework that supports this work are the Mikhail Bakhtin's works, in which the notion of carnavalization and a Bakhtinian theory of laughter are outlined. The study was performed in a documental manner. The research is characterized as qualitative, with an inductive approach, considering the interpretative character of the theoretical perspective used: the dialogical-discursive. We defend the thesis that, unlike the characteristics proposed by Bakhtin (2013) that define carnivalesque laughter, the humor we find today is also a humor that does not overcome oppression but participates in it. What we call black and / or politically incorrect humor often addresses the most socially vulnerable portions of our society. It also reinforces prejudices and stereotypes and does not always present itself as a "weapon in the hands of the people", but rather as a "weapon against the people themselves". We have come to the conclusion that while skits have elements which suggest carnivalization, they do not happen as in the modes presented by Bakhtin because some aspects that lead to the laughable are linked to the ridicularization and stereotyping of certain socially vulnerable groups.